2017
DOI: 10.1007/s00406-017-0850-6
|View full text |Cite
|
Sign up to set email alerts
|

Six-year outcome in subjects diagnosed with attention-deficit/hyperactivity disorder as adults

Abstract: There are very few studies on the long-term outcome in subjects diagnosed with ADHD as adults. The objective of the present study was to assess this and relate the outcome to whether there was current medication or not and to other potential predictors of favourable outcome. A prospective clinical cohort of adults diagnosed with ADHD according to DSM-IV criteria was followed-up on an average of 6 years after first evaluation (n = 124; mean age 42 years, 51% males). ADHD symptom trajectories were assessed as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 54 publications
5
41
1
1
Order By: Relevance
“…Lebensjahr. Im Erwachsenenalter zeigt sich eine ähnlich hohe Komorbiditätsrate von bis zu 75% [Kessler et al, 2006;Kooij et al, 2010;Sobanski und Alm, 2004], insbesondere an Achse-I-(affektive Störungen, Angststörungen, Substanzmissbrauch, Essstörungen, somatoforme Störungen, Anpassungsstörungen [Cumyn et al, 2007]), aber auch Achse-II-(zwanghafte, antisoziale und Borderline-Persönlichkeitsstörungen [Cumyn et al, 2007;Edvinsson et al, 2013;Van Emmerik-van Oortmerssen et al, 2014]) und somatischen Störungen [Spencer et al, 2014].…”
Section: Symptomatik Und Klassifikationunclassified
“…Lebensjahr. Im Erwachsenenalter zeigt sich eine ähnlich hohe Komorbiditätsrate von bis zu 75% [Kessler et al, 2006;Kooij et al, 2010;Sobanski und Alm, 2004], insbesondere an Achse-I-(affektive Störungen, Angststörungen, Substanzmissbrauch, Essstörungen, somatoforme Störungen, Anpassungsstörungen [Cumyn et al, 2007]), aber auch Achse-II-(zwanghafte, antisoziale und Borderline-Persönlichkeitsstörungen [Cumyn et al, 2007;Edvinsson et al, 2013;Van Emmerik-van Oortmerssen et al, 2014]) und somatischen Störungen [Spencer et al, 2014].…”
Section: Symptomatik Und Klassifikationunclassified
“…It has been considered that ADHD prevalence in ASD decreases with age and preliminary data suggest that the association between ASD and ADHD traits may be somewhat lower in adult age than in childhood/adolescence [34]. Current or past diagnosis of ADHD in ASD adult patients has been reported to be from 9.7-43% with most reports being within the range of 37-43% [19] [24] [26] [ [35][36][37] while 10% of a sample of patients diagnosed with ADHD in adulthood had a current or past diagnosis of ASD [38]. Epidemiological and clinical data on the psychiatric comorbidity of this particular group in adulthood are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…Histrionic patients have more alexithymic features compared to a healthy control group (42). For women, previous studies reported higher comorbidity between HPD and ADHD symptoms (43). In a longitudinal study, HPD was related with higher rates of major depression disorder at a subsequent time point (MDD; although the co-occurrence of HDD and MDD is reduced in cross-sectional studies), but in cross-sectional research, HPD was not related with higher suicide risk (44,45).…”
Section: Assessment Of Hpdmentioning
confidence: 82%